2014
DOI: 10.1111/1756-185x.12459
|View full text |Cite
|
Sign up to set email alerts
|

Sleep quality in patients with Behçet's disease

Abstract: Sleep quality is disturbed in patients with BD. The lower quality of sleep is greatly associated with anxiety, depression, QoL, genital ulcers and arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 27 publications
1
26
0
Order By: Relevance
“…[10] In addition, studies focusing on the effect of BD on sleep disturbance and QoL found that patients with BD have reduced sleep quality and QoL. [11][12][13] The findings from the present study are consistent with previous studies for the evolution of depression, anxiety, and QoL in the patients with BD. A significant role of emotional dysfunction was also shown in the course of rheumatic diseases such as BD.…”
Section: Discussionsupporting
confidence: 90%
“…[10] In addition, studies focusing on the effect of BD on sleep disturbance and QoL found that patients with BD have reduced sleep quality and QoL. [11][12][13] The findings from the present study are consistent with previous studies for the evolution of depression, anxiety, and QoL in the patients with BD. A significant role of emotional dysfunction was also shown in the course of rheumatic diseases such as BD.…”
Section: Discussionsupporting
confidence: 90%
“…The results of the study showed that BD patients had increased anxiety, depression and MAF scores compared to the healthy control group. Ertam et al showed that in chronic diseases due to pain, depression and sleep disorders were also present and all of these contributed to a reduced QoL . Yazmalar et al investigated the frequency of depression in BD patients using the HADS, as in the current study .…”
Section: Discussionmentioning
confidence: 79%
“…Behçet's disease (BD) is a systemic inflammatory disorder characterized by recurrent oral and genital ulcers, uveitis, and skin lesions such as erythema nodosum and pustules . Although our understanding of the causes and pathogenesis of BD remains incomplete, the features of BD as an inflammatory multi‐system disease with spontaneous remissions and relapses are similar to those of other autoimmune diseases .…”
Section: Introductionmentioning
confidence: 99%